2016
DOI: 10.1038/jes.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

Use of job-exposure matrices to estimate occupational exposure to pesticides: A review

Abstract: The health effects of pesticides have been extensively studied in epidemiology, mainly in agricultural populations. However, pesticide exposure assessment remains a key methodological issue for epidemiological studies. Besides self-reported information, expert assessment or metrology, job-exposure matrices still appear to be an interesting tool. We reviewed all existing matrices assessing occupational exposure to pesticides in epidemiological studies and described the exposure parameters they included. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 123 publications
(387 reference statements)
0
28
0
1
Order By: Relevance
“…The decline in the use of job title as an EAM might be associated with reduced exposure misclassification. Assessments by job title may introduce bias as, for example, not all farmers apply pesticides, and work tasks may vary during a working life 2 35. Yet a large percentage of documented EAM comprised self-reported exposures, to a high degree applied in studies on self-reported outcomes and cancer, which, particularly in case-control settings, might indicate a large potential of differential misclassification and responder bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decline in the use of job title as an EAM might be associated with reduced exposure misclassification. Assessments by job title may introduce bias as, for example, not all farmers apply pesticides, and work tasks may vary during a working life 2 35. Yet a large percentage of documented EAM comprised self-reported exposures, to a high degree applied in studies on self-reported outcomes and cancer, which, particularly in case-control settings, might indicate a large potential of differential misclassification and responder bias.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure to pesticides has been associated with several health outcomes including cancer,1 2 neurological diseases,3 4 mental disorders,2 rheumatoid arthritis,5 respiratory diseases,6–8 various genetic biomarkers9 10 and reproductive and developmental disorders 3 11. Occupationally exposed populations comprise for example, agricultural workers, gardeners, flower growers, forestry workers and hygiene and pest control workers 12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review (47) summarised various models of JEMs that have been developed over time to assess pesticide exposure. The authors differentiated between JEMs studied specifically for agricultural cohorts, and others that have been produced to assess exposure in the general population.…”
Section: Use Of Job-exposure Matrices and Quantitative Algorithmsmentioning
confidence: 99%
“…The comparison between different JEMs (47) led the authors to the conclusion that these tools can be particularly useful to pesticide toxicology, particularly towards the study of the impact of these toxicants in the development of chronic diseases. Even if the results obtained with the use of JEMs look promising, the literature lacks comparisons between these results and those obtained with other exposure assessment methods.…”
Section: Use Of Job-exposure Matrices and Quantitative Algorithmsmentioning
confidence: 99%